Spatial resolution of a preclinical PET tomograph (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Positron emission tomography (PET) is an important molecular image modality and its application on preclinical research has increased during last decades. Thus, in laboratory practice, it is important to implement a quality control of the equipment, since intrinsic factors influence the image quality. The objective of this work was to perform and implement spatial resolution tests for the small animal PET scanner of the Molecular Imaging Laboratory, LIM/CDTN. Empirically, spatial resolution of a PET scanner can be determined from the measurement of point or linear sources and FWHM (full width half maximum) analysis of the respective linear profiles. In this work, a point source of 22Na and a hot rod style phantom filled with 18F-FDG solution were used. Acquisition and reconstruction of images were performed with the LabPET 1.12.1 software, provided by the equipment manufacturer. Image reconstruction parameters followed the LIM standard protocol: MLEM-3D algorithm, 20 iterations, no high resolution mode, no attenuation or scatter corrections, no post-filtering. PeakFit® and Amide softwares were used to perform images post-processing. The results indicate that the scanner has an adequate spatial resolution and its value is compatible with values reported in international studies performed on similar equipments.